Relationship between appetite levels and anxiety symptoms in chronic hemodialysis patients - Elihud Salazar; Claudia Lerma; Abel Lerma; Tommaso Bochicchio; María Paola Carolina García-Paz (Kidney Research and Clinical Practice, 2012)
Appetite level evaluated by the appetite and diet assessment tool (ADAT) is associated with several clinical and nutritional variables. Our aim was to expand the study to psychological variables (depression symptoms, anxiety symptoms, and distorted thinking). We studied 96 chronic kidney disease patients treated with hemodialysis three times per week. Representative variables are shown as median (percentile 25–percentile 75) or absolute values. DRI = daily recommended intake. Appetite level Very poor, poor (N=10) Fair, Good (N=31) Very Good (N=55) Tau Sex (F/M) 9 / 1 12 / 19* 22 / 33* -- Age (years) 65 (46–2) 50 (29–65) 47 (33–58)* −0.18& Creatinine (mg/dL) 7.4 (6.9–8.6) 11.1 (8.0–13.9)* 11.3 (9.4–13.0)*